2017
DOI: 10.1038/s41598-017-12577-z
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific behavioural synchronization: dogs exhibit locomotor synchrony with humans

Abstract: Behavioural synchronization is widespread among living beings, including humans. Pairs of humans synchronize their behaviour in various situations, such as walking together. Affiliation between dyadic partners is known to promote behavioral synchronization. Surprisingly, however, interspecific synchronization has recived little scientific investigation. Dogs are sensitive to human cues, and share strong affiliative bonds with their owners. We thus investigated whether, when allowed to move freely in an enclose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 45 publications
3
52
1
1
Order By: Relevance
“…However, when we looked at behavioral synchronization between affiliated partners, we found that pet dogs exhibited a high level of behavioral synchronization, whichever breed was tested (e.g., Duranton et al, 2017c), and it may therefore have evolved during early domestication (i.e., before modern artificial selection). Such an hypotheses would be consistent with the fact that no effect of sex was either found on dogs' behavioral synchronization with humans (Duranton et al, 2017a(Duranton et al, , 2018a(Duranton et al, , 2018b(Duranton et al, , 2018c, suggesting that this social skill might have been broadly selected through early domestication in all dogs. It is likely that ability to synchronize with humans, and sensitivity to human's behavioral synchronization, are two skills that have been selected for at different times in dogs' evolutionary history.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…However, when we looked at behavioral synchronization between affiliated partners, we found that pet dogs exhibited a high level of behavioral synchronization, whichever breed was tested (e.g., Duranton et al, 2017c), and it may therefore have evolved during early domestication (i.e., before modern artificial selection). Such an hypotheses would be consistent with the fact that no effect of sex was either found on dogs' behavioral synchronization with humans (Duranton et al, 2017a(Duranton et al, , 2018a(Duranton et al, , 2018b(Duranton et al, , 2018c, suggesting that this social skill might have been broadly selected through early domestication in all dogs. It is likely that ability to synchronize with humans, and sensitivity to human's behavioral synchronization, are two skills that have been selected for at different times in dogs' evolutionary history.…”
Section: Discussionsupporting
confidence: 70%
“…Interestingly, breed never influenced the dogs' behavioral synchronization towards their human referent, whatever the condition. As soon as their owners started moving, the pet dogs engaged in high degree of behavioral synchronization (when walking inside: Duranton et al, 2017a; when walking outside: Duranton et al, 2017b; when encountering an unfamiliar person, approach condition, and retreat condition: Duranton et al, 2016). Moreover, when shelter dogs displayed behavioral synchronization, we found no influence of breed group on their behavior (Duranton et al, 2017b).…”
Section: Effect Of Genetic Selection On Behavioral Synchronization Skmentioning
confidence: 49%
See 3 more Smart Citations